2019
DOI: 10.21203/rs.2.11938/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Weight Management among School-Aged Children and Adolescents: A Quantitative Assessment in a Ghanaian Municipality

Abstract: Background: Childhood and adolescent overweight, obesity and underweight have become an issue of grave concern to both the developed and developing countries in context of global burden of non-communicable diseases. Unhealthy weight status is a significant public health issue for developing countries, of which Ghana is not excluded. This study evaluated the prevalence of overweight, obesity and underweight and its related factors among school-aged children and adolescents. Methods: A total of 1004 participants… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In the present study, we could not substantiate the findings of Moubarac et al [ 13 ] as the 2014 DHS data did not include food intake or snacking habits. Nevertheless, a recent study in the Bekwai Municipality of Ghana indicated that snacking before bed increased the odds of overweight/obesity by more than ten times for 5–17 years children; girls were more overweight (19.4% vs. 7.6%, p < 0.001) and obese (10.2% vs. 7.3%, p = 0.177) compared to boys in this study [ 35 ]. The data on physical activity in the present study may not well reflect the usual physical activity behaviour of our sample.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In the present study, we could not substantiate the findings of Moubarac et al [ 13 ] as the 2014 DHS data did not include food intake or snacking habits. Nevertheless, a recent study in the Bekwai Municipality of Ghana indicated that snacking before bed increased the odds of overweight/obesity by more than ten times for 5–17 years children; girls were more overweight (19.4% vs. 7.6%, p < 0.001) and obese (10.2% vs. 7.3%, p = 0.177) compared to boys in this study [ 35 ]. The data on physical activity in the present study may not well reflect the usual physical activity behaviour of our sample.…”
Section: Discussionmentioning
confidence: 51%
“…Conversely, it may be that girls who watched TV frequently were better informed about healthy behaviours. Gyamfi et al [ 35 ] recently found TV watching protective of overweight/obesity in southern Ghana. Like Zimmerman and Bell [ 46 ], Gyamfi and colleagues [ 35 ] argued that the content of TV shows rather than TV watching itself is associated with poor nutrition outcomes since adolescents who watch educative programmes may be more educated.…”
Section: Discussionmentioning
confidence: 99%